Ermita Cartagena a tribute portfolio hotel by Marriott implementation of new quotation tools in the sales process (2022)
Chapter 9: Conclusion During my time as an intern I gained a lot of knowledge, which is being very useful for my professional and personal life. The excellent management I have of every space in the hotel, my great ability to present every corner, my confidence when dealing with a client or guest, my agility to solve problems and conflicts that may arise during events or group arrivals, are a lot of positive things that will mark me forever. Especially the opportunity to leave my mark, to know that if, at some point, I am no longer at Ermita, a part of me will be present in that department. Someone new will use my format and make quotes and share the brochure and it will be partly thanks to me that their work will be a little easier, thanks to my idea and dedication they will have an incredibly functional and practical tool. It is something extremely meaningful to me. Ermita was, is and will continue to be that home and school that opened the doors and gave me the opportunity to learn, to grow, to set clear goals and decide my path, Ermita took me out of that need I had to complete my stage as a practitioner, but it also gave me and continues to give me the best learning opportunities, Ermita became my second home and I can proudly say that after 8 months as an intern I was hired as Events Coordinator and today after a year of experience the doors of a new position are open to me as Coordinator of groups and events, I know it is an exponential growth, but it has been sweated and worked with the greatest of dedication and I certainly do not regret one day having made the decision to go out into the streets and deliver resumes and much less I regret having done my job and that of others just to get where I am.